Augmentation of Pectoral Fin Teratogenicity by Thalidomide in Human Cytochrome P450 3A-Expressing Zebrafish - Wenjing Dong; Ippo Akasaka; Akifumi Komiyama; Tatsuro Nakamura; Naohiro Mizoguchi; Tasuku Nawaji; Shinichi Ikushiro; Makoto Kobayashi; Hiroki Teraoka (Pharmaceuticals, 2023)
The pharmacological and toxicological effects of active metabolites of enzymes including cytochrome P450 (CYP) are important. While it has been believed for a long time that thalidomide causes characteristic limb malformation only in rabbits and primates including humans, the involvement of their CYP3A subtypes (CYP3As) has been suggested. Recently, however, it was reported that zebrafish were sensitive to thalidomide, showing defects of pectoral fins, homologous organs of forelimbs in mammals, as well as other deformities. In this study, we prepared human CYP3A7 (hCYP3A7)-expressing zebrafish (F0) using a transposon system. Thalidomide caused pectoral fin defects and other malformations including pericardial edema in hCYP3A7-expressing embryos/larvae but not in wild-type and hCYP1A1-expressing embryos/larvae. Thalidomide also reduced the expression of fibroblast growth factor 8 in pectoral fin buds in only hCYP3A7-expressing embryos/larvae. The results suggest the involvement of human-type CYP3A in thalidomide teratogenicity.